2012
DOI: 10.1089/dia.2011.0244
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Its Chronic Complications in the She Ethnic Minority Group of China

Abstract: Objective: According to recent reports, the development of type 2 diabetes in China has soared at an alarming rate. However, most of the investigations were based on Han people, who account for the majority of people in China. Little is known about the prevalence of diabetes its chronic complications in the She people, who have their own traditional lifestyle and hereditable background, different from other Asian population. The present study investigated the prevalence of type 2 diabetes and associated risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…In contrast with some other studies, we did not find an association of polyneuropathy with IFG. Most studies that suggested an association between pre-diabetes and polyneuropathy lacked a control group,4–8 or did not control for age, which is strongly related to both polyneuropathy and (pre)diabetes 10 34 35. One controlled study did show an association of IGT and neuropathy,9 while the majority of controlled studies, especially the studies that took the confounding effect of age into account, found no association 11–13 15 25 30 31 36.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with some other studies, we did not find an association of polyneuropathy with IFG. Most studies that suggested an association between pre-diabetes and polyneuropathy lacked a control group,4–8 or did not control for age, which is strongly related to both polyneuropathy and (pre)diabetes 10 34 35. One controlled study did show an association of IGT and neuropathy,9 while the majority of controlled studies, especially the studies that took the confounding effect of age into account, found no association 11–13 15 25 30 31 36.…”
Section: Discussionmentioning
confidence: 99%
“…However, an age- and sex-matched, population-based MONICA (Monitoring Trends and Determinants on Cardiovascular Diseases)/KORA (Cooperative Research in the Region of Augsburg) study of subjects aged 25–74 years showed prevalence of polyneuropathy in 7.4% of those with normal glucose tolerance, 11.3% of those with IFG, 13.0% of those with IGT, and 28.0% of the diabetic subjects [25]. More recently, another age- and sex-standardized epidemiological study in the She Ethnic Minority Chinese subjects aged ≥20 to ≤80 years old revealed prevalence of polyneuropathy in 16.1% of those had IFG, 13.1% had IGT, 18.6% had both IFG and IGT, and 28.4% had diabetes [11]. Others have questioned the link between prediabetes and polyneuropathy.…”
Section: Introductionmentioning
confidence: 98%
“…In China, along with 9.7% diabetes prevalence, the number of prediabetic people has been estimated at 148.2 million adults, accounting for 15.5% of the population [10]. Furthermore, the prevalence of both prediabetes and diabetes is age-dependent with the peak of prediabetes (50–60 years old) being ten years earlier than that for diabetes (60–70 years old) [10], [11], supporting the existence of pre-clinical processes in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…In China, a study on the She ethnic minority group revealed the prevalence of polyneuropathy in impaired fasting glucose (IFG), impaired glucose tolerance (IGT), IFG/IGT, and diabetes mellitus (DM) to be 16.1%, 13.1%, 18.6%, and 28.4% respectively, which are greater than that in patients with normal glucose tolerance (NGT) [3]. A study on a Western population revealed that the prevalence of neuropathic pain was 13.3%, 8.7%, 4.2%, and 1.2% in normal subjects and subjects with diabetes, IGT, and IFG, respectively [4].…”
Section: Introductionmentioning
confidence: 99%